A new species of Metrosideros (Myrtaceae) from Vanuatu and notes on the genus - Pillon, Yohan (Phytotaxa, 2018)
Metrosideros Banks ex Gaertner (1788: 170, Myrtaceae) is one of the most widespread tree genus across the Pacific islands and is an emerging model for the study of speciation in tropical trees (Papadopulos et al. 2011; Stacy et al. 2014). The material housed at the Muséum National d’Histoire Naturelle in Paris (P) was recently reviewed in order to prepare the evaluation of the New Caledonian species for the IUCN redlist (IUCN 2017) and apply some recent taxonomic changes in the genus (Pillon et al. 2015). A new species from Vanuatu came to light and is described below.